POLÍTICAS LINGUÍSTICAS NA COLÔNIA “ALEMÃ” DE ENTRE RIOS: O PAPEL DO COLÉGIO IMPERATRIZ DONA LEOPOLDINA - Vecchia, Adriana Dalla (2013)
This work investigates how language teaching policies are thought at the College Imperatriz Dona Leopoldina, situated in the multilingual region of Entre Rios, Guarapuava/PR, starting with the language policies adopted by the community, and then observe what relationship there is between these policies and beliefs of the language somehow involved with the institution context. Therefore, sat down in ethnographic research, in a qualitative/interpretative approach linked to applied linguistics, considering that we are concerned with explaining the intricacies of social relationships, considering that human actions depends on the meanings assigned to him by social players. The analyzes were made possible through the intersection of collected data by the following methodological tools: close ended questionnaire, semi-structured interviews and classroom observations. Participants were German and Portuguese teachers, plus a mentioned pedagogical institution coordination representative, students, a college sponsor representative and also a community representative. The theoretical apparatus that enabled the analysis is linked to the discussions on Linguistic Policies and Planning (CALVET, 2002, 2007), the Applied Linguistics (Cavalcanti, 1999); MAHER 2007, FINGER, 2008) and guidelines regarding Linguistic Beliefs and Attitudes (BARCELOS, 2004; BARCELOS, Abraham, 2006) and other theorists and explainers. Data analysis allowed us to state that: a) Colonia Entre Rios can be considered as multilingual once can be seen in the community the use of Schwowisch, Portuguese and Hochdeutsch language; b) the entry of the Portuguese and the advancement of Hochdeutsch taught in school have done to regress Schwowisch language use, so, by extension, the multilingualism situation in the future, can make room to a bilingualism situation of Hochdeutsch/Portuguese at least among young people in the community who attended/attend Colégio Imperatriz; c) multilingualism is stigmatized within school; d) bilingualism Hochdeutsch/Portuguese is considered by the school community as a linguistic ideal condition and thus raises higher status within the community; e) Hochdeutsch and the Portuguese have higher status than Schwowisch within the community of Entre Rios; f) within the College, according to the participants themselves, the role of teachers of English and German language is distinct in terms of achieved results; g) although Portuguese language teachers claiming to act in accordance with the theoretical and methodological approaches proposed by the institution and the educational chosen material, they have not exceeded expectations of pedagogical coordination; h) Finally, the community through its representatives is satisfied with both German and Portuguese teaching as well as with the positive results obtained by students in proficiency exams, contest and ENEM. So with this research, we hope had contributed to discussions about Entre Rios linguistically similar situations and also through the survey results, benefited school relationship within the mentioned community, in such a way that the conflictual relations between the linguistic community and the surrounding Swabian group may be at least better understood.